Women Leadership and Motivation at Madrasa - Dewi, Asmara; Ayu, Sovia Mas; Patimah, Siti; Akmansyah, Muhammad; Thahir, Andi (Journal of Advanced Islamic Educational Management, 2022)
Women's leadership has a significant role in achieving the successful implementation of activities that take place in the madrasa. Motivation is very important in increasing the morale and productivity of employees, the higher the motivation of a person to carry out work, the higher the productivity. The purpose of this study is to describe women's motivational leadership at Madrasa Ibtidaiyah Negeri in Lampung Selatan Regency, Indonesia. The research data were collected through the process of interviews, observation, and documentation through primary data sources, namely female madrasa heads in the State Madrasa Ibtidaiyah and their deputies, teachers, and staff of the State Madrasa Ibtidaiyah in South Lampung Regency, and a number of books, brochures, websites, and examples of previous research related to this research. Data sources in this study were selected purposefully through snowball sampling. Data analysis was carried out through the processes of data reduction, data presentation, and conclusion drawing. Data validity checks in this study were carried out by triangulating with sources. The results show that the leadership of women in Madrasa Ibtidaiyah Negeri of South Lampung Regency can be said to have been able to motivate their subordinates. Motivation of subordinates is done in several ways, namely: (a) setting the physical environment, (b) setting the work atmosphere, (c) modeling discipline, (d) encouraging, (e) giving awards, and (f) providing learning resources.